A Reference Framework to Establish and Sustain Onlife Communities and Its Use - Nektarios Moumoutzis; Yiannis Sifakis; Stavros Christodoulakis; Desislava Paneva-Marinova (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2019)
This paper employs the overarching concept of communities to express the social contexts within which human creativity is exercised and learning happens. With the advent of digital technologies, these social contexts, the communities we engage in, change radically. The new landscape brought about by digital technologies is characterized by new qualities, new opportunities for action, new community affordances. The term onlife is adopted from the Onlife Manifesto and used to distinguish the new kind of communities brought about by the modern digital technologies, the Onlife Communities . Design principles are presented to foster such communities and support their members. To showcase the use of these design principles, the paper presents a concrete system addressing creativity and learning in the field of cultural heritage (history teaching and learning): ViSTPro. ViSTPro enables the visualization of spatiotemporal processes, thus facilitating active learning of historical events. To demonstrate the flexibility of the ViSTPro and its capability to provide insightful visualizations, a pilot application has been elaborated on the Battle of Marathon, 490 BC.